“Un caballo desbocado”: el devenir animal en Los cuerpos del verano de Martín Felipe Castagnet - Martínez Molina, Ana Lucía (2022)
The novel Los cuerpos del verano (2012), by Martín Felipe Castagnet, takes up the traditional bodysoul dualism and constructs a society in which the internet reconfigures, based on a mercantilist logic, the notions of life and death. It is a capitalist context in which people can separate consciousness from bodies through technology and migrate to others according to their economic capacity to acquire them. After occupying two dysfunctional human bodies, Rama, the protagonist, migrates into the body of a horse, whose form and identity he eventually embraces. This bodily journey involves a process of material and affective learning at the same time. This article analyzes the biopolitical dimension of the novel based on the residual materiality of human bodies and marginalized spaces and discusses the animal becoming that admits the figure of the horse as a fetish of corporal domestication or resistance to the dictate of hyper-technified utility.